Optimization of Seal Steam Turbine Pressure Control on CCPP Boiler System Using Fuzzy-PID Auto-Tuning Method - Muhammad Barkah; Bambang Suprianto; Unit Three Kartini (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2026)
This study optimizes the High-Pressure to Turbine Seal Steam Pressure Control Valve system in a Combined Cycle Power Plant to address nonlinear characteristics and fluctuating load dynamics. Conventional fixed-gain controllers structurally fail to manage these conditions effectively. We propose a hybrid Relay Feedback with Fuzzy-PID strategy, employing a quantitative simulation design validated with industrial data from the Muara Tawar CCPP. Using a First Order Plus Dead Time model, the method integrates Relay Feedback for initial parameter identification and Fuzzy Logic for real-time PID adjustment. Evaluated via MATLAB/Simulink across various scenarios, the hybrid approach yielded superior transient performance, outperforming metaheuristic benchmarks (Particle Swarm Optimization (PSO), Ant Colony Optimization (ACO)) in stabilizing the system. Crucially, validation against real operational data demonstrated that the proposed method eliminated oscillatory valve behavior, yielding a massive improvement in actuator energy efficiency and significantly reducing the Root Mean Square Error (RMSE). The novelty lies in integrating Relay Feedback autotuning with Fuzzy self-tuning PID, explicitly validated using real operational data. This practical approach provides robust control and extends actuator lifespan by mitigating mechanical wear.